The clinical relevance of severe thermal artefacts in specimens after LLETZ: Klinični pomen obsežno termično poškodovanih robov stožca po LLETZ - Cokan, Andrej; Žebeljan, Ivan; Serdinšek, Tamara; Pakiž, Maja (Acta Medico-Biotechnica, 2022)
Purpose: Large loop excision of the transformation zone (LLETZ) under local anaesthesia has almost replaced cold knife conisation in the treatment of cervical squamous intraepithelial dysplasia (SIL). Thermal artefacts in specimens after LLETZ may be so severe, that they prevent histopathological interpretation and evaluation of the radicality of the procedure. There are limited data regarding the prevalence of severe thermal artefacts after LLETZ and their clinical relevance regarding the need for reoperation.Methods: In this retrospective study, we included 314 consecutive patients who were treated with LLETZ or cold knife conisation for cervical SIL in 2016 at our clinic. The primary outcome of the study was to determine the prevalence of severely damaged surgical margins after LLETZ and if these thermal artefacts can predict residual disease or the need for reoperation. The secondary outcome was the prevalence of postoperative and short–term complications.Results: Three hundred and fourteen women underwent surgery for cervical SIL. In 95.2% of cases, we performed LLETZ, and 89.3% of women had this procedure under local anaesthesia. The reoperation rate was 3.8%. Positive or inconclusive margins were present in 20.4% of specimens. In 10.7% of allLLETZ cases, thermal artefacts were so severe that they interfered with histopathological interpretation. However, only one of these patients needed reoperation. Postoperative vaginal discharge and mild bleeding requiring therapeutic intervention occurred in 4.7% and 6.7% of cases, respectively.Conclusion: Although approximately 10% of patients had severe thermally damaged margins after LLETZ, only 3% required reoperation. In our experience, severely damaged margins were not associated with higher reoperation rate. On the other hand, a carefully planned follow–up visit with cytology, human papillomavirus (HPV) testing and colposcopy with biopsy after the procedure is of utmost importance in the evaluation of residual disease.
Keywords: precancerous lesions of the uterine cervix, postoperative complications, surgical margins